2016
DOI: 10.1086/688765
|View full text |Cite
|
Sign up to set email alerts
|

Color Change for Thermoregulation versus Camouflage in Free-Ranging Lizards

Abstract: Animal coloration has multiple functions including thermoregulation, camouflage, and social signaling, and the requirements of each function may sometimes conflict. Many terrestrial ectotherms accommodate the multiple functions of color through color change. However, the relative importance of these functions and how colorchanging species accommodate them when they do conflict are poorly understood because we lack data on color change in the wild. Here, we show that the color of individual radio-tracked bearde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 56 publications
2
68
2
Order By: Relevance
“…S1). Previous experiments on temperature-dependent colour change showed 1-2% change in UV reflectance across all individuals (Smith et al, 2016a), despite greater visible colour change than detected here. Separate experiments (Smith et al, 2016a) quantifying colour change during handling based on nearsimultaneous photographs and spectral measurements confirmed that the distribution of colours of lizards in RGB colour space was statistically similar to the distribution of colours in avian or lizard visual colour space (Smith et al, 2016a).…”
Section: Processing and Analysis Of Photographic Datacontrasting
confidence: 66%
See 3 more Smart Citations
“…S1). Previous experiments on temperature-dependent colour change showed 1-2% change in UV reflectance across all individuals (Smith et al, 2016a), despite greater visible colour change than detected here. Separate experiments (Smith et al, 2016a) quantifying colour change during handling based on nearsimultaneous photographs and spectral measurements confirmed that the distribution of colours of lizards in RGB colour space was statistically similar to the distribution of colours in avian or lizard visual colour space (Smith et al, 2016a).…”
Section: Processing and Analysis Of Photographic Datacontrasting
confidence: 66%
“…Previous experiments on temperature-dependent colour change showed 1-2% change in UV reflectance across all individuals (Smith et al, 2016a), despite greater visible colour change than detected here. Separate experiments (Smith et al, 2016a) quantifying colour change during handling based on nearsimultaneous photographs and spectral measurements confirmed that the distribution of colours of lizards in RGB colour space was statistically similar to the distribution of colours in avian or lizard visual colour space (Smith et al, 2016a). Those experiments were done using the same captive lizards from Mildura and Alice Springs as used in this study and validate the use of linearised and equalised RGB data from standard photographs to approximate variation perceived by avian predators or conspecifics (Smith et al, 2016a).…”
Section: Processing and Analysis Of Photographic Datacontrasting
confidence: 66%
See 2 more Smart Citations
“…Second, RGB values were equalised relative to the 20% grey standard in each image to account for slight variation in illumination (Stevens et al 2007). Further details of the linearisation and equalisation method are given in Stevens et al (2007), Garcia et al (2013) and Smith et al (2016). We then calculated the standardised difference between the R and G channels as (R − G) / (R + G + B), which was defined as x, and the G and B channels as (G − B) / (R + G + B), which was defined as y.…”
Section: Data Collectionmentioning
confidence: 99%